0766 Evaluation Of Cataplexy-free Days In Children/Adolescents With Narcolepsy With Cataplexy Treated With Sodium Oxybate. (12th April 2019) - Mignot, Emmanuel; Rosen, Carol L; Menno, Diane; Wang, Grace; Profant, Judi; Dauvilliers, Yves
Abstract: Introduction: Cataplexy resolves in some patients with narcolepsy when treated with sodium oxybate (SXB). A post-hoc analysis was conducted to determine the number of cataplexy-free days/week experienced by participants in a placebo-controlled, randomized-withdrawal study evaluating SXB treatment in children/adolescents with narcolepsy with cataplexy. Methods: SXB-naïve participants were titrated to an optimal dose of SXB, then entered a stable dose period (SD) for 2 weeks; participants on SXB entered the SD on their usual dose of SXB for 3 weeks. After a 2-week double-blind, placebo-controlled randomized-withdrawal period (DB), participants entered an open-label safety period (OL) for total duration of 1 year or less. Cataplexy-free days/week were calculated from daily cataplexy diaries completed by participants during each study period. Safety was also assessed. Results: Of 106 participants, 69.8% were SXB naïve and 30.2% were on SXB at enrollment. In SXB-naïve participants, the number (median [Q1, Q3]) of cataplexy-free days/week increased over the titration period: 0.0 [0.0, 2.0] week 1, 1.0 (0.0, 3.0) week 2, 4.0 (1.0, 6.0) last 7 days; n=71. During the last 14 days of the SD, the number of cataplexy-free days/week remained stable and was similar in participants who were SXB naïve or on SXB at study entry: 4.3 (1.0, 5.8), n=66 and 4.8 (0.8, 6.5), n=32, respectively. During the last week of the DB, the number of cataplexy-free days/week decreased to 0.0 (0.0, 2.7) in participants randomized to placebo (n=32) but remained stable at 4.0 (1.0, 6.0) in participants continuing SXB (n=31). The number of cataplexy-free days then remained stable throughout the OL. Common adverse events (>10%) in the safety population (n=104) were enuresis, nausea, vomiting, headache, and decrease in weight. Conclusion: SXB treatment increased the number of cataplexy-free days/week in children/adolescents with narcolepsy with cataplexy. The safety profile of SXB in this study was consistent with previous studies in adult and pediatric narcolepsy. Support (If Any): Jazz Pharmaceuticals.